Bridging preclinical and clinical gut microbiota research using the ex vivo SIFR® technology - Van den Abbeele, Pieter; Deyaert, Stef; Thabuis, Clémentine; Perreau, Caroline; Bajic, Danica; Wintergerst, Eva; Joossens, Marie; Firrman, Jenni; Walsh, Dana; Baudot, Aurélien (Frontiers in Microbiology, 2023)
While modulation of the human adult gut microbiota is a trending strategy to improve health, the underlying mechanisms are poorly understood. This study aimed to assess the predictive value of the ex vivo, reactor-based, high-throughput SIFR (Systemic Intestinal Fermentation Research) technology for clinical findings using three structurally different prebiotics (inulin (IN), resistant dextrin (RD) and 2’-fucosyllactose (2’FL)). The key finding was that data obtained within 1-2 days were predictive for clinical findings upon repeated prebiotic intake over weeks: amongst hundreds of microbes, IN stimulated Bifidobacteriaceae, RD boosted Parabacteroides distasonis, while 2’FL specifically increased Bifidobacterium adolescentis and Anaerobutyricum hallii. In line with metabolic capabilities of these taxa, specific SCFA were produced thus providing insights that cannot be obtained in vivo where such metabolites are rapidly absorbed. Further, in contrast to using single or pooled fecal microbiota (approaches used to circumvent low throughput of conventional models), working with 6 individual fecal microbiota enabled correlations that support mechanistic insights. Moreover, quantitative sequencing removed the noise caused by markedly increased cell densities upon prebiotic treatment, thus allowing to even rectify conclusions of previous clinical trials related to the tentative selectivity by which prebiotics modulate the gut microbiota. Counterintuitively, not the high but rather the low selectivity of IN caused only a limited number of taxa to be significantly affected. Finally, while a mucosal microbiota (enriched with Lachnospiraceae) can be integrated, other technical aspects of the SIFR technology are a high technical reproducibility, and most importantly, a sustained similarity between the ex vivo and original in vivo microbiota. By accurately predicting in vivo¬ results within days, the SIFR technology can help bridge the so-called ‘Valley of Death’ between preclinical and clinical research. Facilitating development of test products with better understanding of their mode of action could dramatically increase success rate of microbiome modulating clinical trials.